2015
DOI: 10.1016/j.fm.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antifungal activity of Lactobacillus harbinensis K.V9.3.1Np and Lactobacillus rhamnosus K.C8.3.1I in yogurt

Abstract: Few antifungal protective cultures adapted to fermented dairy products are commercially available because of the numerous constraints linked to their market implementation. Consumer's demand for naturally preserved food products is growing and the utilization of lactic acid bacteria is a promising way to achieve this goal. In this study, using a 2(5-1) factorial fractional design, we first evaluated the effects of fermentation time, of initial sucrose concentration and of the initial contamination amount of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Yeast and moulds are shown to be the determinant of the shelf life of pasteurized cream and their count can be linked to doming of yogurt containers [4]. Despite the off-flavour and changes in visual appearance of dairy products, fungal contamination can lead to the significant economic losses [5]. Additionally, the introduction of fruit into yogurts can amplify the risk of spoilage by yeasts by providing additional sources of contamination and fermentable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Yeast and moulds are shown to be the determinant of the shelf life of pasteurized cream and their count can be linked to doming of yogurt containers [4]. Despite the off-flavour and changes in visual appearance of dairy products, fungal contamination can lead to the significant economic losses [5]. Additionally, the introduction of fruit into yogurts can amplify the risk of spoilage by yeasts by providing additional sources of contamination and fermentable substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported the promising potential of LAB as protective cultures for inhibiting pathogenic and spoilage bacteria in many food systems. In this context, a total inhibition of yeast contamination has been observed by Delavenne and others () when Lactobacillus harbinensis K.V9.3.1Np was added as a bioprotective agent in yogurt. Likewise, Cheong and others () reported the effectiveness of Lactobacillus plantarum isolates in controlling the growth of Penicillium commune on cottage cheese for up to 18 d at room temperature.…”
Section: Natural Antimicrobial Agents For Food Preservationmentioning
confidence: 85%
“…These results are in accordance with previous findings, which showed that some LAB (including the Lactobacillus harbinensis K.V9.3.1Np, Lactobacillus brevis NS01, Lactobacillus casei AST18, and Lactobacillus rhamnosus K.C8.3.1I) have antimicrobial efficiency against foodborne pathogens and spoilage microorganisms in food products. [38,48,49] 6.13 ± 0.08 Aa 5.10 ± 0.10 Cb ND ND ND Nd presented not detected. Different lowercase letters (a-d) in the same row show significant differences (P < 0.05) between different storage time.…”
Section: Biopreservation Of Fermented Soybean Milk During 21 D Storagementioning
confidence: 90%